Analysis of Sustainable Marketing Dimensions on Purchase Intention: Social, Environmental, Economic, and Cultural Responsibility (A Study of Prospective Electric Vehicle Consumers in Jakarta) - Aldo Esa Kusuma; Arief Bowo Prayoga Kasmo (ARE Publisher, 2026)
Objectives: Electric vehicles have been promoted as a sustainable transportation solution; however, consumer purchase intention in Jakarta remains relatively low, indicating a gap between sustainability policies and actual consumer behavior. This study aims to analyze the effect of sustainable marketing dimensions—social, environmental, economic, and cultural responsibility—on prospective consumers’ intention to purchase electric vehicles. Methodology: This research adopts a quantitative approach using a survey method. Data were collected through an online questionnaire from 217 respondents selected using purposive sampling, consisting of prospective EV consumers aged 20–40 years, residing in Jakarta, and familiar with electric vehicles. The collected data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.14 to examine the direct effects of sustainable marketing dimensions on purchase intention. Findings: The results indicate that social, environmental, economic, and cultural responsibility all have a positive and significant effect on purchase intention. Economic and environmental responsibility exert the strongest influence, while social and cultural responsibility also positively contribute by fostering moral attachment, trust, and alignment with societal norms. Conclusion: Purchase intention toward electric vehicles in Jakarta is shaped by multiple dimensions of sustainable marketing. Effective strategies to encourage adoption should integrate economic, environmental, social, and cultural initiatives to enhance perceived value, trust, and cultural alignment. This highlights the importance of a holistic sustainable marketing approach rather than focusing solely on incentives or technical features. Keywords: Sustainable marketing; Social responsibility; Environmental responsibility; Economic responsibility; Purchase intention.